Pengaruh Lama Simpan Bakso Ayam dengan Level Substitusi Filler Tepung Gembili terhadap Kualitas Organoleptik dan Total Mikroorganisme: Effect of Long Storage of Chicken Meatballs with Gembili Flour Filler Substitution Level on Organoleptic Quality and Total Microorganisms - Sukma, Nuraeni Ayu; Mudawaroch, Roisu Eny; Zulfanita, Zulfanita (Jurnal Riset Agribisnis dan Peternakan, 2025)
Processed meatball products generally use meat and flour as raw materials, one of which is gembili flour. This study aims to determine the effect of shelf life of chicken meatballs with the level of substitution of gembili flour filler on the organoleptic quality and total microorganisms of chicken meatballs. The research method used was Completely Randomized Design (CRD) factorial pattern, involving 30 semi trained panelists as respondents. The focus of the research was chicken meatballs with 5 levels of gembili flour substitution (0, 25, 50,75, and 100%) and 4 shelf-life treatments (day 0, 5, 10, and 15) at a temperature of 5°C refrigerator. The data obtained were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT). The results showed that the level of substitution of gembili flour gave a very significant effect on color, aroma, and significantly different from texture, chewiness, and taste in the organoleptic test. Shelf life showed a very significant effect on aroma, texture, taste, and significantly different from color and had no significant effect on elasticity. The substitution of gembili flour had a very significant effect on color and aroma, and significantly different on texture, chewiness and taste in hedonic quality. Shelf life gave a very significant effect on color, aroma, chewiness and significantly different from texture and taste in hedonic quality. The interaction between substitution level and shelf life did not show significant differences on color in organoleptic quality, but had a very significant effect on aroma, texture, chewiness and taste. Their interaction gave a very significant effect on all parameters in hedonic quality. Substitution level and shelf life can increase the total number of microorganisms. The conclusion of this study shows that gembili flour substitution can improve organoleptic quality and extend the shelf life of meatballs